Tracer Study of Arabic Language Education Alumni of Institut Agama Islam Negeri Sultan Amai Gorontalo - I. Miolo, Mukhtar (Assuthur: Jurnal Pendidikan Bahasa Arab, 2023)
This Article discusses the tracer study of Arabic language education alumni of the Sultan Amai Gorontalo State Islamic Institute. The formulation of the problem in this study is how the alumni profile in the world of work and how stakeholders respond to alumni performance. This research includes descriptive quantitative research using the survey method. This research was conducted through google form with 113 alumni respondents and 9 stakeholders. The research instrument used was a questionnaire, the data analysis technique used percentages and a Likert scale. Based on the results of the study, the profile of alumni who completed the undergraduate education program was 89% and 11% continued the master's education program, 84% of the alumni had found work, 92% worked as education personnel, with a waiting period of less than 3 months 56% and those who had worked before graduating 24%. As for the responses regarding stakeholders related to alumni performance regarding the seven aspects, namely ethics, expertise in the field of science, use of information technology, teamwork, and self-development, most of them have received very good responses from stakeholders.